Towards compressive and tensile strengths of hybrid steel and PVA fibre-reinforced cementitious composites: Experimental and analytical - Gang Chen; Mingyan Lv; Haitang Zhu; Jianwen Zhang; Le Zhang (Case Studies in Construction Materials)
Hybrid fibre-reinforced cementitious composites (HFRCCs) have demonstrated super engineering performance in terms of strengths, toughness, ductility and durability since the hybrid fibre effect can be positively activated when the hybrid ratio of polyvinyl alcohol (PVA) and steel fibres falls in an appropriate range. However, the appropriate hybrid ratio for achieving a positive hybrid effect needs to be explored. In addition, currently available analytical/statistical models for predicting the strength of HFRCCs are far from satisfactory and, therefore, need to be improved. In this study, compressive and flexural tensile tests were carried out to investigate the compressive and flexural tensile strengths of HFRCCs. The experimental results show that increasing the water/cement ratio would dramatically reduce the compressive strength of HFRCCs, but marginally reduce their flexural tensile strength. With the steel fibre volume ratio up to 0.75 vol%, the HFRCCs with 0.15 vol% steel fibres and 1.5 vol% PVA fibres exhibit the highest compressive and flexural tensile strengths. With the PVA fibre volume ratio up to 1.5 vol%, the flexural tensile strength of HFRCCs increases but their compressive strength decreases with the increase of the PVA fibre volume ratio. The hybrid fibre effect on compressive and tensile strengths collected from the literature was calibrated and compared by using four analytical models for strength. Their performance was evaluated against the experimental data from this study and the literature. Then, the hybrid fibre ratio (in terms of volume fraction) for the best hybrid effect on HFRCC strength was proposed. Through analysing numerous experimental data from this study and the literature, an analytical model that can explicitly consider fibre volume fraction and fibre aspect ratio was modified to predict the compressive and tensile strengths of HFRCCs. It has been found that the modified analytical model gives a better prediction of compressive and flexural tensile strengths of HFRCCs.